Analisis Strategi Marketing dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Online Shop Berbasis Aplikasi Shopee pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam UIN Raden Intan Lampung - Anisa Dwi Cahyani; Nina Agustiani; Yogi Aprianto; Anas Malik (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This study aims to analyze the influence of marketing strategies and customer trust on purchasing decisions in Shopee-based online shops among students of the Faculty of Islamic Economics and Business, UIN Raden Intan Lampung. The research employs a qualitative method with a literature study approach, collecting data from various relevant literatures, journals, and documents. The findings reveal that effective marketing strategies, such as discount promotions, loyalty programs, and influencer engagement, significantly affect purchasing decisions. Moreover, customer trust, which is built on transaction security, product quality, and customer reviews, plays a crucial role in enhancing purchasing decisions. The study concludes that the collaboration between innovative marketing strategies and customer trust is essential for creating an optimal online shopping experience.